An Investigation of the Interests and Reasons of Diploma Nurses Undertake a RN-BSN Bridging Program in United Arab Emirates - Muhammad Arsyad Subu; Reetha Ismail; Jacqueline Maria Dias; Mini Sara Abraham; Imam Waluyo; Maryuni Maryuni; Djadjang Aditaruna; Slamet Soemarno (Faculty of Nursing Universitas Padjadjaran, 2020)
The nursing programs across United Arab Emirates are in the process to inform students about RN-BSN bridging program. The study purpose was to determine the interests and reasons of nurses in enrolling to a RN –BSN bridging program. An online survey was conducted among diploma students to explore their interest and perspective regarding pursuing bridging program. One hundreds thirty-five RNs participated. The questionnaire used for survey had seventeen items, which included questions to elicit information or clarification of their perspectives. We performed the data analysis in SPSS by computing descriptive and inferential statistics. The findings showed that a majority of nurses were interested in returning to RN-BSN program. The students’ reasons were both personal and career related, with personal reasons being more dominant. Most of participants held a diploma and midwifery and they had more than 2 years working experience since they completed diploma. There appears to be a need for a RN-BSN bridging program because most of study respondents are potential candidates for this program. This study provides information to nursing schools’ management to provide opportunities and develop curriculums to meet the needs of these nurses. Nurses need to reflect on various strategies for incorporating their new knowledge into clinical practice.